Encyclopedia of Clinical Neuropsychology - Kreutzer, Jeffrey S.; DeLuca, John.; Caplan, Bruce; SpringerLink (Online service) (New York, NY : Springer New York, 2011)
Clinical neuropsychology is a rapidly evolving specialty whose practitioners serve patients with traumatic brain injury, stroke and other vascular impairments, brain tumors, epilepsy and nonepileptic seizure disorders, developmental disabilities, progressive neurological disorders, HIV- and AIDS-related disorders, and dementia. . Services include evaluation, treatment, and case consultation in child, adult, and the expanding geriatric population in medical and community settings. The clinical goal always is to restore and maximize cognitive and psychological functioning in an injured or compromised brain. Most neuropsychology reference books focus primarily on assessment and diagnosis, and to date none has been encyclopedic in format. Clinicians, patients, and family members recognize that evaluation and diagnosis is only a starting point for the treatment and recovery process. During the past decade there has been a proliferation of programs, both hospital- and clinic-based, that provide rehabilitation, treatment, and treatment planning services. This encyclopedia will serve as a unified, comprehensive reference for professionals involved in the diagnosis, evaluation, and rehabilitation of adult patients and children with neuropsychological disorders.
Assessment strategies -- Behavioral syndromes and disorders -- Biographies of leading professionals in the field -- Care systems -- Diagnosis and diagnostic labels -- Educational and vocational issues -- Accommodations. - Forensic issues -- General issues -- Imaging modalities and techniques -- -Medical issues -- Medications -- Movement disorders -- Neurological disorders and injuries -- Neurological syndromes -- Professional issues -- Rehabilitation interventions -- Test batteries -- Tests and assessment tools.
Keywords: Medicine; Neurology; Psychology, clinical; Developmental psychology; Consciousness; Medicine & Public Health; Neuropsychology; Neurology; Child and School Psychology; Cognitive Psychology; Health Psychology